(untitled) (Revista Brasileira Multidisciplinar, 2024)
Among the various side effects resulting from chemotherapy, the most frequent complication is oral mucositis (OM), defined as an inflammation of the inside of the mouth, resulting in pain, erythema and / or ulcers and often related to depression and anxiety. The objective of this research was to verify possible correlations between psychological variables and pain threshold in cancer patients affected by OM. Pilot study was carried out, with a sample established by convenience using the criteria: assessment of OM using the World Health Organization (WHO) scale and Oral Mucositis Assessment Scale (OMAS); visual analogue pain scale (VAS); assessment of pain threshold using an analog algometer; Depression, anxiety and stress scale-21 (DASS-21) e; Beck scales .; these instruments were applied at three different times. The sample consisted of 11 individuals, with a median age of 56 years. The statistically relevant results were observed in the second moment of the research, through the following tests: EVA (p = 0.018), DASS-21 (anxiety scale p = 0.039), BDI (p = 0.044) and BAI (p = 0.043). When presenting OM and low pain threshold, the participants also presented depression and anxiety. We can conclude that individuals with cancer, submitted to chemotherapy treatment, who develop oral mucositis and present a lowering of the pain threshold, present depression and anxiety during antineoplastic treatment.